PENGARUH PENGETAHUAN WAJIB PAJAK, KESADARAN WAJIB PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN PELAKU E-COMMERCE DALAM MEMENUHI KEWAJIBAN PERPAJAKAN (STUDY KASUS WAJIB PAJAK ORANG PRIBADI PELAKU UMKM DI KOTA BUKITTINGGI) - Anisa Sapitri; Habibatur Ridhah (Jurnal Ekonomi dan Bisnis, 2025)
The aim of this research is to examine the influence of mandatory knowledge, taxpayer awareness and tax sanctions on taxpayer compliance in e-commerce business actors in Bukittinggi City. This type of research is quantitative. The object of this research is taxpayer knowledge, taxpayer awareness, tax sanctions and taxpayer compliance of e-commerce users. The primary data source is in the form of respondents’ answers to a questionnaire and the secondary is in the form of determining the population through the website so that a sample of 45 respondents is obtained. The unit of analysis used is individuals, namely taxpayers carrying out e-commerce businesses in Bukittinggi City. The data analysis used is descriptive statistics, data quality testing, classical assumption testing, and hypothesis testing using SPSS version 29. The results of this research show that taxpayer knowledge partially has a positive andsignificant effect on taxpayercompliance with e- commerceusers, then taxpayer awarenessand tax sanctionspartially have noeffect on taxpayercompliance with e-commerce users. Simultaneous test results, namely knowledge of tax regulations, taxpayer awareness and taxsanctions together (simultaneously) have a significant positive effect on e-commerce taxpayer compliance.